Aquaculture Practices and Knowledge Level of Fish Farmers in Purulia District of West Bengal - Nilanjan Rej; Shyam Sundar Dana; Abdul Hannan Mondal; Moumita Ray Sarkar; Dipam Ray; Arif Ahammed; Ritika Karjee (Indian Journal of Extension Education, 2025)
The study was conducted in the Purulia district of West Bengal during 2024–25, aimed to assess the state of aquaculture and the knowledge level of fish farmers. 120 fish farmers were individually interviewed to collect primary data. Most ponds were earthen (90.83%), rain-fed (68.33%), and seasonal (56.67%), with water retention for 6 to 9 months. Indian major carp were farmed by 86.67% of the respondents through polyculture systems. Only 15% used commercial feed, and 77.5% monitored fish growth throughout the culture period. It was also revealed that 38.33% had a medium level of knowledge, while 34.17% had a low level of knowledge about recommended fish farming practices. It was further found that education, occupation, farming experience, mass media exposure, extension agency contacts, and economic motivation had strong relationships with the respondents’ knowledge level (p<0.01). The majority of respondents faced constraints such as inadequate technical support for scientific fish farming (RBQ: 86.09) and high costs of input materials and skilled labour (RBQ: 85.4). A concerted educational effort with follow-up, stronger extension services, input subsidies, better water retention infrastructure, and mass media awareness is urgently needed in the area.